INVESTIGATION OF ANAEROBIC PROCESSES IN SEPTIC TANK AS A WASTEWATER TREATMENT OPTION - Osigbemhe, Itofa-Oghena; Usman, Rufai; Ochi, Marycynthia Kosarachukwu; Oladejo, Samuel Taiwo; Osalumese, Godspower; Osigbemhe, Ikpaobo-Oghena (FUDMA JOURNAL OF SCIENCES, 2025)
The demand for quality drinking water is a necessity across the world today considering the high level of increase in population and global warming. It is therefore necessary to adopt different alternative measures in converting wastewater into drinkable water. This project therefore aimed at investigating the anaerobic processes in septic tank as a wastewater treatment option using wastewater from a septic tank-: a case study of Etsako West Local Government Area of Edo State. Personal observation and laboratory analysis were used for data collection. Water samples were taken from a septic tank to assess the level of temperature, conductivity, pH, odour, COD, BOD, and OD in the water. The result showed the presence of BOD in the water sample was higher (106.6883 mg/L) than the WHO tolerance limit of 5 mg/L for drinking water. The sample was heavily loaded with colloidal matter (turbidity: 42.09 NTU), organic matter (COD: 106 mg/L), and suspended matter (turbidity: 42.09 NTU). This shows that the discharge of septic tank effluent to water bodies without treatment poses a serious health risk to humans and the environment. Therefore, the following recommendations were made: provision of adequate waste disposal facilities to cater for both solid and liquid waste, enforcement of existing health and hygienic regulations guiding abattoir operation.